(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Gestational diabetes mellitus (GDM) is a common pregnancy complication with complex disease mechanism. Several risk factors may contribute to its onset. Based on recent evidence up-to 15% of all pregnancies may be affected by GDM. Untreated GDM is a severe threat to maternal and neonatal health Objectives: To determine the risk factors and foeto- maternal outcome of GDM. Methods: This prospective observational study was conducted on patients who were admitted in Obstetrics & Gynaecology department of CMH, Bogura from June 2020 to May 2021 with the diagnosis of GDM. Data were collected from the patients as well as from the antenatal records in a preformed questionnaire and risk factors and outcomes measured. Results: A total of 679 patients were admitted during the period of 1 year from June 2020 to May 2021. Among them 50 patients were admitted with GDM. The prevalence of GDM was 7.36%. GDM risks were higher in women aged between 25-29 years and in those with maternal overweight and obesity (58%). Newborns of GDM mother had an increased risk of hypoglycemia (10%), macrosomia (20%), respiratory distress syndrome (8 %) and 42% required NICU admission. Most of the patients (92%) needed cesarean section. Conclusion: Pre-pregnancy BMI and family history of diabetes in first degree relatives and high parity were the predominant risk factor of GDM in this study. GDM patients are of increase risk of delivery by cesarean section, preterm birth, Newborns of GDM mother are at risk of RDS (Respiratory distress syndrome), macrosomia and neonatal hypoglycemia. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 46-50